Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1037/a0012856
|View full text |Cite
|
Sign up to set email alerts
|

Fostering partner dependence as trust insurance: The implicit contingencies of the exchange script in close relationships.

Abstract: A model of the trust-insurance system is proposed to examine how low and high self-esteem people cope with the interdependence dilemma posed by feeling inferior to a romantic partner. Feeling inferior automatically activates "if-then" contingencies that link inferiority to the exchange script (i.e., partner qualities are evenly traded) and exchange script anxieties to reparative efforts to secure a partner's dependence. A daily diary study of newlyweds and five experiments supported the model. Induced upward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 109 publications
3
101
0
1
Order By: Relevance
“…Research has also shown, however, that people sometimes respond to threatened regard or feelings of inferiority with compensatory activities (e.g., taking on a chore) that aim at restoring a partner's dependence(Murray et al, 2009). 2 The amount of money y which was returned by the experimenter was related to x and the ratio of returned money was determined in advance so that all participants ended up with a payoff between 1.60€ and 2.60€.…”
mentioning
confidence: 98%
“…Research has also shown, however, that people sometimes respond to threatened regard or feelings of inferiority with compensatory activities (e.g., taking on a chore) that aim at restoring a partner's dependence(Murray et al, 2009). 2 The amount of money y which was returned by the experimenter was related to x and the ratio of returned money was determined in advance so that all participants ended up with a payoff between 1.60€ and 2.60€.…”
mentioning
confidence: 98%
“…Serving as a means to multiple goals should: (a) make people feel that their partners are more dependent on them, thus enhancing feelings of security (e.g., Murray, Aloni et al, 2009); (b) make people confident that even if they lose the ability to be instrumental in one domain or if their partner no longer pursues a particular kind of goal, they will still be able to offer their partner other things; (c) make it harder for partner to find an alternative partner who could do all of the things they do for the partner.…”
Section: Implications For the Person Serving As A Meansmentioning
confidence: 99%
“…People who responded to feeling inferior by doing communal favors for their partner also had partners who reported greater commitment to them the next day [12].…”
Section: The Functionality Of the Rulesmentioning
confidence: 98%
“…For the "ensure-mutual-dependence" rule, we activated feelings of inferiority to the partner (IF) by implicitly priming the exchange script [12]. In one experiment, participants in A c c e p t e d M a n u s c r i p t 7 the "inferiority" condition (IF) reviewed personal ads that touted the importance of partners making an even exchange [20].…”
Section: Revealing the Automatic Rulesmentioning
confidence: 99%
See 1 more Smart Citation